Profile of astigmatism in school going children at state level hospital in Uttarakhand - Gupta, Manisha; Vats, Vatsala; Tyagi, Rupali (International Journal of Research in Medical Sciences, 2016)
Background: Astigmatism is a clinically important condition and accounts for about 13% of the refractive errors of the eye. Its prevalence has been reported to vary with ethnicity, age, and sex. The aim of this study was to evaluate the profile of astigmatism in school going children and compared with similar studies in India and Asian countries. Methods: This was prospective cross – sectional hospital based study. The children aged between 5-13 years of age attending the eye OPD during the period of one year, were screened for visual acuity. Those with visual acuity <20/40 were selected for detailed ocular examination. Statistical analysis was done by (IBM SPSS version 23) percentage and chi square test. Results: Of the total 409 children, astigmatism was found to be present in 222 (54.27%) cases, of which 109 (49.09%) were males and 113 (50.90%) were females, With the Rule astigmatism was present in 188 (84.69%), Against The Rule astigmatism was present in 34 (15.32%) of cases. Conclusions: Our present study showed that the single most common refractive error in primary school age children was astigmatism and emphasizes the need for more effective and regular school screening programmes.